Hammer throwing (countering dynamics) - Maheras, A. (Techniques Magazine, 2023)
During a hammer throw, the athlete first rotates the hammer two or three times around his body while keeping both feet on the ground. Following, the athlete attempts to increase the speed of the hammer by turning three or four times together with it, as one system, while being in double and single support alternately. During the turns, as the throw progresses and the speed of the thrower + hammer system increases, the athlete will be "countering" the hammer to maintain an optimum balance of the system. He can do this by employing two methods, a.) countering with the "hips" which involves the reaching out with the arms and shoulders, while at the same time the midsection area is brought backwards (figure 1), or b.) countering with the "shoulders" which involves the tilting of the torso more or less backwards with the hips in a neutral or forward position (figure 2). Employing one or the other countering method will affect the radius of rotation of the hammer in that, the more the backward tilt, the more the reduction in the hammer radius (Dapena, 1989).